Total site heat integration incorporating the water sensible heat - Liew, Peng Yen (Elsevier, 2014)
Analysis of steam and water losses in the Total Site (TS) utility system is critical in process industry. Makeup water plays an important role in maintaining the water balance in the steam and condensate systems. Total Site Heat Integration (TSHI) offers a solution to increase energy savings as well as energy efficiency and consequently, to promote sustainability. However, so far most studies on TSHI have not considered the water sensible heat in TS targeting; e.g. for Boiler Feed Water (BFW) preheating and steam superheating during steam generation. In this work, an extended methodology is developed to target the minimum utility requirements in a steam system that considers the water sensible heat. The Extended Total Site Problem Table Algorithm (TS-PTA) is proposed as a systematic numerical tool to consider the sensible heat while targeting the Total Site utility requirements. The Extended Site Composite Curves (ESCC) are developed as a visualisation tool for the Extended TS-PTA. Illustrative and industrial case studies are used to verify the methodology. The results demonstrate the significance of considering the sensible heat of water on the TS utility targets.